Effect of Tannic Acid Extracted from Cassava (Manihot esculenta Crantz) Leaves on Productive Performance, Intestinal Microorganisms and Villi Morphometry in Broilers: A Preliminary Study - Aengwanich , Worapol; Boonsorn, Thongchai (International Journal of Poultry Science, 2017)
Background and Objective: Cassava, Manihot esculenta Crantz (Euphorbiaceae) leaves contained plentiful of tannic acid. The objective of this study was to investigate the effect of tannic acid extracted from cassava leaves on productive performance and ecology within the small intestines of broilers. Materials and Methods: An in vivo experiment was conducted to study the effect of tannic acid extracted from cassava leaves on productive performance, intestinal microflora and gut morphology in broilers. Treatments included an antibiotic-free diet (control group), a positive control diet and an antibiotic-free diet with tannic acid extracted from cassava leaves at 10, 20, 30, 40 and 50 mg L–1 in drinking water. Body weight, feed intake, average daily gain and feed conversion ratio were investigated for 6 weeks. At week 6, digesta pH, Lactobacillus spp., E. coli populations and villi height of the duodenum, jejunum and ileum were examined. Results: The results revealed the following: The feed intake of broilers fed a positive control diet was lower than that of broilers fed an antibiotic-free diet with tannic acid at 10, 20 and 40 mg L–1 in drinking water (p